Aproximación dialectológica a la lengua cashibo-cacataibo (pano) - Zariquiey, Roberto (2011)
Cashibo-Cacataibo is a Panoan language spoken in the Peruvian Amazon. Despite its relatively small number of speakers this language features a rich dialectal diversity. Although this dialectal situation has previously been documented by G. Tessmann and L. Wistrand, among others, in this article we aim to offer an approach to the dialectology of this language from firsthand data and with an emphasis on the documentation of the phonological aspects that determine the isoglosses separating the Cashibo-Cacataibo dialects. The paper also include references to lexical and morphosyntactic aspects. The conclusions from the data we have collected converge with the results obtained by other scholars: the Cashibo-Cacataibo language consists of four extant dialects (plus an extinct one) with varying degrees of similarity between them.